Controlling sharpness, SNR, and specific absorption rate for 3D fast-spin echo at 7T by end-to-end learning - Dawood, Peter; Blaimer, Martin; Herrler, Jürgen; Liebig, Patrick; Weinmüller, Simon; Malik, Shaihan; Jakob, Peter M.; Zaiß, Moritz (Magnetic Resonance in Medicine, 2025)
Purpose: To non-heuristically identify dedicated variable flip angle (VFA) schemes optimized for the point-spread function (PSF) and SNR of multiple tissues in 3D FSE sequences with very long echo trains at 7T. Methods: The proposed optimization considers predefined specific absorption rate (SAR) constraints and target contrast using an end-to-end learning framework. The cost function integrates components for contrast fidelity (SNR) and a penalty term to minimize image blurring (PSF) for multiple tissues. By adjusting the weights of PSF/SNR cost-function components, PSF- and SNR-optimized VFAs were derived and tested in vivo using both the open-source Pulseq standard on two volunteers as well as vendor protocols on a 7T MRI system with parallel transmit extension on three volunteers. Results: PSF-optimized VFAs resulted in significantly reduced image blurring compared to standard VFAs for T2-weighted while maintaining contrast fidelity. Small white and gray matter structures, as well as blood vessels, were more visible with PSF-optimized VFAs. Quantitative analysis shows that the optimized VFA yields 50% less deviation from a reference PSF (sinc) than the standard VFA. The SNR-optimized VFAs yielded images with significantly improved SNR in a white and gray matter region relative to standard (77.1 vs. 40.7, respectively) as trade-off for elevated image blurring. Conclusion: This study demonstrates the potential of end-to-end learning frameworks to optimize VFA schemes in very long echo trains for 3D FSE acquisition at 7T in terms of PSF and SNR. It paves the way for fast and flexible adjustment of the trade-off between PSF and SNR for 3D FSE.
CRIS-Team Scopus Importer:2025-06-06
Keywords: fast spin echo; optimal control; sequence optimization; ultra high field; variable flip angles